Two new Micronola Amsel, 1935 from China and Malaysia (Lepidoptera, Erebidae, Hypenodinae, Micronoctuini). Taxonomic study of Micronoctuini. Contribution III. - Han, Hui Lin; Kononenko, Vladimir S. (Zootaxa, 2021)
N/A